The effect of training, leadership effectiveness and work environment on employee performance in the Procurement of Goods and Services Section of the Regional Secretariat of North Konawe Regency - Ruswanto, Ruswanto; hajar, Ibnu; Hakim, Abdul (PT. Riset Press International, 2024)
This study examines the influence of training, leadership effectiveness, and work environment on employee performance in the Goods and Services Procurement Section of the Regional Secretariat of North Konawe Regency. The method used is a quantitative approach with multiple linear regression. The population of this study includes all 31 employees of the Procurement Section, who also served as the sample for this research. Data was collected through a questionnaire using a Likert scale, then analyzed with statistical tests. The results show that training, leadership effectiveness, and the work environment collectively have a positive and significant impact on employee performance. Individually, each variable was also proven to positively and significantly affect performance. This study emphasizes that improving the quality of training provided, leadership effectiveness, and a comfortable work environment play a significant role in enhancing employee performance. These findings can serve as a reference for government agencies in formulating more effective employee development strategies.